ORIGIN AND EVOLUTION OF THE CONCEPT «SUBURBAN AREA» - Олійник, Валентина (Human Geography Journal, 2016)
The article deals with the origin, evolution of the concept of "suburban area". Served first studies on this subject in Western Europe and the USA. The main direction of the study subjects’ Suburban area. "Based on the analysis, marked the stages of development of suburban areas are a few definitions. As a generalization based on foreign and domestic references a table structure suburbs, held parallel to the English versions of definitions Ukrainian, criteria for the selection of structural elements suburban areas and key processes of structural elements.